Основні напрями розвитку підприємств овочівництва - Занозовська, Оксана Григорівна (My University, 2019)
На основі аналізу діяльності підприємств овочівництва Рівненської області визначено основні напрями ефек- тивного розвитку підприємств. На виробництво продукції овочівництва впливає багато чинників: екологічні, економічні, соціальні тощо. Пріоритетний напрям розвитку овочівництва в сучасних умовах – виробництво у закритому ґрунті, особливість виробництва –міжсезонний характер. Перспективи виробництва продукції ово- чівництва визначено на основі розрахункових економічних методів. The article defines the main directions of effective development of vegetable growing enterprises. It is determined that the production of vegetable products depends on many factors, including from the structure of the crop area. The priority direction in the development of effective vegetable growing is the production of products in closed soil, since it creates conditions for round-the-year production, including organic products. On the basis of the method of trend extrapolation, the prospects for the production of vegetable production for two years have been determined. Ensuring the population of the country qualitative, safe and affordable food depends on the efficiency of activities in the agrarian sector. The necessity of vegetable production is connected with the definition of the directions of development of enterprises of vegetable growing. This requires the creation of conditions for their effective development in priority areas, which envisage the unity of economic, social and environmental interests of society.
Keywords: розвиток; напрями; овочівництво; продукція; підприємство; виробництво; ефекктивність; development; vegetable growing; production; enterprise; productivity; кафедра міжнародної економіки